Analysing the non-linear effects of learning traits on knowledge transfer in international outsourcing alliances: the case of suppliers in emerging markets. (5th November 2014) - Wu, Wei-Li; Lee, Yi-Chih
This study applied multivariate adaptive regression splines (MARS) to explore the non-linear relationships between suppliers' learning traits and knowledge transfer in international outsourcing alliances. There are five learning traits included in this study: organisational learning intent, employee learning intent, self-learning commitment, manufacturing ability and integrated databases. Through a dataset of 206 suppliers, this study revealed that organisational learning intent, employee learning intent, self-learning commitment and integrated databases have non-linear and positive influences on knowledge transfer, while manufacturing ability has a non-linear and negative influence on knowledge transfer. Therefore, suppliers eager to learn could enhance their performance in knowledge transfer by paying more attention to their learning traits.